Therapeutic Drug Monitoring of Meropenem and Piperacillin in Critical Illness-Experience and Recommendations from One Year in Routine Clinical Practice - Christina Scharf; Michael Paal; Ines Schroeder; Michael Vogeser; Rika Draenert; Michael Irlbeck; Michael Zoller; Uwe Liebchen (MDPI AG, 2020)
Various studies have reported insufficient beta-lactam concentrations in critically ill patients. The extent to which therapeutic drug monitoring (TDM) in clinical practice can reduce insufficient antibiotic concentrations is an ongoing matter of investigation. We retrospectively evaluated routine meropenem and piperacillin measurements in critically ill patients who received antibiotics as short infusions in the first year after initiating a beta-lactam TDM program. Total trough concentrations above 8.0 mg/L for meropenem and above 22.5 mg/L for piperacillin were defined as the breakpoints for target attainment. We included 1832 meropenem samples and 636 piperacillin samples. We found that 39.3% of meropenem and 33.6% of piperacillin samples did not reach the target concentrations. We observed a clear correlation between renal function and antibiotic concentration (meropenem, r = 0.53; piperacillin, r = 0.63). Patients with renal replacement therapy or creatinine clearance (CrCl) of <70 mL/min had high rates of target attainment with the standard dosing regimens. There was a low number of patients with a CrCl >100 mL/min that achieved the target concentrations with the maximum recommended dosage. Patients with impaired renal function only required TDM if toxic side effects were noted. In contrast, patients with normal renal function required different dosage regimens and TDM-guided therapy to reach the breakpoints of target attainment.